A conceptual framework for assessing the impact of human behaviour on water resource systems performance - Shanono, Nura Jafar; Ndiritu, John (جامعة الوادي - university of el oued, 2020)
The persistent poor performance of water resource systems (WRS) has been reportedly linked to not only climate change and dilapidated water infrastructures but also human unlawful activities. Some of these unlawful activities include unauthorized water abstractions, wastage, excessive losses, discharging untreated wastewater, over‐application of chemicals and fraudulent incidences. Despite advances in WRS planning and operational analysis, incorporating such undesirable activities to quantitatively assess their impact on WRS performance remain elusive. This study was then inspired by the need to develop a methodological framework for WRS performance assessment that integrated human impacts with WRS analysis tasks. A conceptual framework for assessing the impact of human behaviour on WRS performance using the concept of socio-hydrology is proposed herein. The framework identifies and coupled four major sources of water values (WRS, goals, managers and users) using three activities serving as the missing links between these values (interactions, outcomes and feedbacks). The framework can be used as a database for choosing relevant social and hydrological variables and to understand the inherent relations between the selected variables to study a specific human-water problem in the context of WRS management.
Article
Keywords: Conceptual framework; Human behaviour; Socio-hydrology; Water resource systems.